Boundary Work in the Space of Personal Social Services: Concepts, Challenges and Opportunities - Gevorgianienė, Violeta; Šumskienė, Eglė; Genienė, Rasa; Žalimienė, Laimutė; Dunajevas, Eugenijus (Socialinė teorija, empirija, politika ir praktika, 2024)
In the face of external threats, Lithuania's personal social services system must adapt to ensure the continued delivery of services. It must respond to the need to change the content of services, expand the scope of services to include new clients, attract or admit new social service providers, and manage the boundaries between formally provided social services and other individuals and organizations offering assistance. The aim of this article is to define the concepts of 'boundaries' and 'boundary work' in the context of personal social services' resilience to external threats and to investigate how actors from different social spaces—formal (institutionalized) social service providers and non-formal (non-institutionalized) social assistance providers—characterize their interactions with each other and perform 'boundary work'. Research methods include interviews and focus groups. Research participants comprise: 1) formal social service providers (8 focus groups), and 2) informal actors operating in municipalities of different sizes (10 interviews). The study revealed that crises lead to shifts in the boundaries between the activities of different social service providers, increased interactions between actors from different social spaces, the creation of new cooperation networks, emerging opportunities for action, and limitations in their activities. In this phase of challenges and the search for solutions, new social service providers emerge and the contours of new forms of assistance take shape. Reflecting on the experience of crises allows for the construction of future projections for possible recurrent threats.
Keywords: personal social services; social space; boundary work; crisis; resilience